Ethnobotanical Survey of Medicinal Plants Utilised by the People of Bhola District in Bangladesh - Rabbi, Rifat Hasan; Talukder, Farjana (Journal of Agricultural Sciences (Belgrade), 2026)
This ethnobotanical survey documents medicinal plant diversity and traditional knowledge in Bhola District, Bangladesh, a deltaic ecosystem underrepresented in ethnobotanical literature. Semi-structured interviews were conducted with 100 informants between June and December 2025, recording plant species, preparation methods, and therapeutic applications. In total 39 medicinal plant species from 28 families were documented, with Combretaceae and Lamiaceae being the most prevalent families (7.69% each). Trees (35.9%) and herbs (33.3%) were the dominant growth forms, while leaves (43.3%) and fruits (22.4%) were the most utilised plant parts. Decoction (46.2%) and juice extraction (23.1%) were the primary preparation methods. Relative frequency of citation (RFC) analysis revealed Allium sativum (0.85), Aloe vera (0.82), and Curcuma longa (0.73) as the most culturally significant species. Informant consensus factor (ICF) values ranged from 0.67 to 0.91, with digestive disorders (0.91), respiratory diseases (0.88), and skin diseases (0.86) showing the highest consensus. These findings provide baseline data for the evidence-based integration of traditional medicine into healthcare frameworks and identify priority species for phytochemical investigation and conservation management in this vulnerable deltaic ecosystem.
Keywords: Medicinal Plants; Traditional Knowledge; Ethnobotany; Agricultural Knowledge; Barisal Division in south-central Bangladesh